Late Weichselian and Holocene record of the paleoenvironmental changes in a small river valley in Central Poland. (1st March 2016) - Pawłowski, Dominik; Borówka, Ryszard K.; Kowalewski, Grzegorz A.; Luoto, Tomi P.; Milecka, Krystyna; Nevalainen, Liisa; Okupny, Daniel; Tomkowiak, Julita; Zieliński, Tomasz
Abstract: The developmental history, from the Oldest Dryas to the Late Holocene, of a paleolake and mire located in a river valley in Central Poland was studied using high-resolution records of pollen, macrofossils, Cladocera, sedimentology, and geochemistry from a 14 C dated sediment core. We inferred temperature and water level dynamics using cladocerans and palynological and geochemical methods were employed to investigate natural fluvial activity, particularly for these elements that are difficult to find through sedimentological methods. Our research demonstrates how climate fluctuation in the Late Glacial and Holocene periods influenced the development of a paleolake and mire in a small river valley and shows the importance of long-term research to establish hydroclimatic conditions in biogenic sediments. We propose that water level fluctuations were important in modifying biotic assemblages. The results of our multiproxy analysis clearly suggest that the main driver of changes in aquatic and terrestrial ecosystems, as well as in geomorphological processes in the valley, was climate: reconstructed temperatures generally follow the known trends, showing an increase at the beginning of the Bølling, Allerød, and Holocene and a decrease at the beginning of the Oldest and Younger Dryas. Similarly, periods of water level increase are synchronous with climatic changes. However, the local environmental forces were a significant factors affecting biotic diversity in the studied time span. Fish predation, macrophyte structure, pH, and calcium content partly influence the results of the cladoceran-based water depth reconstruction in particular. Interestingly, the cladoceran-inferred summer temperature reconstruction for Pawłowa appear realistic. Although the temperature trends can be considered reliable, our results indicate the important role of local factors which control the species composition of the subfossil assemblages. Highlights: Environmental drivers of Late Glacial and Holocene valley development. Cladoceran-inferred summer temperature and water-depth reconstruction. Water-level changes and denudation were significant in floodplain development. Fish predation, macrophyte structure, and CaCO3 content distort reconstructions. Fens and paleolakes on floodplains as a key for paleoclimate studies.